The role of parenting stress in anxiety and sleep outcomes in toddlers with congenital heart disease - Lepage, Charles; Gaudet, Isabelle; Doussau, Amélie; Vinay, Marie-Claude; Gagner, Charlotte; von Siebenthal, Zorina; Poirier, Nancy; Simard, Marie-Noëlle; Paquette, Natacha; Gallagher, Anne (Frontiers in Pediatrics, 2023)
Objectives This retrospective cohort study investigates how parenting stress, measured at 4 months of age by use of a classic three-dimensional parent-reported scale (Parenting Stress Index, 4th Ed. or PSI-4), can predict anxiety symptoms and quality of sleep at 24 months in toddlers with congenital heart disease (CHD). Study Design Sixty-six toddlers with CHD followed at our cardiac neurodevelopmental follow-up clinic were included in this study. As part of their systematic developmental assessment program, parents completed questionnaires on their stress level (PSI-4) when their child was 4 months old, and on their child's anxiety symptoms and quality of sleep at 24 months. Eight multiple linear regression models were built on the two measures collected at 24 months using the PSI-4 scores collected at 4 months. For each measure, four models were built from the PSI-4 total score and its three subscales (Parental Distress, Parent-Child Dysfunctional Interaction, Difficult Child), controlling for sex and socioeconomic status. Results The PSI-4 Difficult Child subscale, which focuses on parenting anxiety related to the child's behavioral problems and poor psychosocial adjustment, accounted for 17% of the child's anxiety symptoms at 24 months. The two other PSI-4 subscales (Parental Distress and Parent-Child Dysfunctional Interaction) and the PSI-4 total score did not contribute significantly to the models. None of the four regression models on perceived quality of sleep were significant. It is important to note that 33% of parents responded defensively to the PSI-4. Conclusions Parenting stress related to the child's behavioral problems and poor psychosocial adjustment, measured when the child is 4 months old, is associated with the child's ulterior anxiety symptoms. As very few standardized tools are available to assess the behavioral and psychoaffective development of infants, this study highlights the importance of early psychosocial screening in parents of infants with CHD. The high rate of significant Defensive Responding Indices reminds us to not take parent reports at face value, as their actual stress levels might be higher.